Climate effects on fish body size–trophic position relationship depend on ecosystem type. Issue 9 (27th June 2019) - Dantas, Danyhelton D. F.; Caliman, Adriano; Guariento, Rafael D.; Angelini, Ronaldo; Carneiro, Luciana S.; Lima, Sergio M. Q.; Martinez, Pablo A.; Attayde, José L.
Abstract : The energetic demand of consumers increases with body size and temperature. This implies that energetic constraints may limit the trophic position of larger consumers, which is expected to be lower in tropical than in temperate regions to compensate for energy limitation. Using a global dataset of 3635 marine and freshwater ray‐finned fish species, we addressed if and how climate affects the fish body size–trophic position relationship in both freshwater and marine ecosystems, while controlling for the effects of taxonomic affiliation. We observed significant fish body size–trophic position relationships for different ecosystems. However, only in freshwater systems larger tropical fish presented a significantly lower trophic position than their temperate counterparts. Climate did not affect the fish body size–trophic position relationship in marine systems. Our results suggest that larger tropical freshwater fish may compensate for higher energetic constraints feeding at lower trophic positions, compared to their temperate counterparts of similar body size. The lower latitudinal temperature range in marine ecosystems and/or their larger ecosystem size may attenuate and/or compensate for the energy limitation of larger marine fish. Based on our results, temperature may determine macroecological patterns of aquatic food webs, but its effect is contingent on ecosystem type. We suggest that freshwater ecosystems may be more sensitive to warming‐induced alterations in food web topology and food chain length than marine ecosystems.